Exploring Home-School Partnership through Epstein's Framework: A comparative study of two post primary schools. - Dunwoody, Anna Marie (Trinity College Dublin. School of Education. Discipline of Education, 2022)
Historically the role of parents in the Irish education system has not been part of a planned programme of partnership but the result of unlinked government policies and initiatives which involved parents in school life. The concept of partnership with parents has changed in Ireland and there is greater understanding of the benefits it provides to students. Partnership is now recognised as a key aspect of school planning and self-evaluation in post-primary schools. The aim of this research is to investigate partnership with parents at post-primary level and to explore the occurrence of partnership and the extent to which it is planned by schools with the purpose of improving student outcomes. Epstein?s partnership framework was utilised as an indicator for evaluating partnership activities occurring in the participating schools. The research approach taken was an evaluation of partnership with parents in two schools with contrasting settings. A case study approach was taken combining quantitative and qualitative methods to develop an understanding of social construction related to partnership with parents. The case study schools reflected a similarity as regards parents? perception of partnership. Findings indicate that despite a majority of parents? desire to be involved in their child?s post-primary school, this was not a reality. Parents and teachers demonstrated a lack of a common understanding of what partnership is, and limited evidence of partnership was displayed in the schools despite a commitment to partnership by management in both schools. In order to develop partnership, the case study schools need to explicitly inform parents about partnership with the school: how parent participation affects student success and the variety of partnership opportunities available to parents. Utilising Epstein?s partnership framework would be a support; as this research indicates, it has a useful application in the Irish context. Findings suggest that if these post-primary schools are to fulfil their obligation as outlined in LAOS (2016a), SSE (2016c) and be prepared for the Education (Student and Parent Charter) Bill 2019, they must develop a planned and coordinated approach to partnership with parents. Recommendations provided build on current activities within the schools which are linked to partnership with parents. Utilising Epstein?s partnership framework as a continuum would allow the schools to engage in focused planning for increased opportunities for partnership with parents which are linked to student outcomes.
APPROVED
Keywords: Partnership; partnership with parents; partnership framework; Joyce Epstein; post-primary schools